GROWTH AND PRODUCTION OF SWEET CORN PLANTS (Zea mays saccharata. Strut) FROM THE EFFECT OF FERMENTATION OF SEVERAL MIXTURES OF PALM OIL MILL SOLID WASTE (LPKS) WITH COW SOLID (LTS) - Sembiring, Meriksa; Risdawati Ginting (Journal of Innovation Research and Knowledge, 2023)
The research was carried out in Sei Mecirim Village Market 4 Sunggal District with an altitude of + 400 meters above sea level, Andosol soil type, the research will be carried out from July to September 2023. With the research title "Growth and production of sweet corn (Zea mays saccharata. Strut) From the Effect of Some Fermentation of Palm Oil Mill Solid Waste (LPKS) Mixture with Cow Solid Waste". This study used a non-factorial Group Randomized Design (RAK) with 5 mixed treatments of LPKS with LTS Cattle Waste were So (without LPKS and LTS), S1 (30% LPKS + 70% LTS), S2 (50% LPKS + 50% LTS), S3 (70% LPKS + 30% LTS), S4 (100% LPKS) and S5 (100% LTS) using 4 repeats and at a dose of 14 tons/ha. Based on the results of the research conducted differences in substitution have a real influence on the growth and production of sweet corn, To get the best growth and production, use 70% LPKS with 30 5